Myeloid Derived Suppressor Cells: Key Drivers of Immunosuppression in Ovarian Cancer - Baert, Thaïs; Vankerckhoven, Ann; Riva, Matteo; Van Hoylandt, Anaïs; Thirion, Gitte; Holger, Gerhardt; Mathivet, Thomas; Vergote, Ignace; Coosemans, An (Frontiers in Immunology, 2019)
The presence of tumor infiltrating lymphocytes (TILs) is associated with a longer overall survival in advanced stage epithelial ovarian cancer. Despite the prognostic impact of TILs, response to checkpoint-inhibitors and antigen-specific active immunotherapy is limited in ovarian cancer. The goal of our study was to investigate the interaction between ovarian cancer and the innate and adaptive immune system in the ID8-fLuc syngeneic ovarian cancer mouse model. For the in vivo experiments C57BL/6, B6.129S7-Rag1tm1Mom/J and B6.129P2(SJL)-Myd88tm1.1Defr/J mice were inoculated with ID8-fLuc. In vivo depletion experiments were performed using clodronate liposomes (CL), anti-CD8a, anti-GR1, anti-colony stimulating factor 1 (anti-CSF1) and TMβ1 (anti-CD122). Immune read out was performed by fluorescent activated cell sorting analysis for effector T cells, regulatory T cells, natural killer cells, B cells, macrophages and myeloid derived suppressor cells (MDSC), immunohistochemistry for MDSC and tumor-associated macrophages (TAM) and immunofluorescence for M1 and M2 TAM in the vascular context. The effect of MDSC on T cell proliferation and phenotype were studied in vitro. We discovered that the absence of T and B cells did not influence tumor growth or survival of B6.129S7-Rag1tm1Mom/J mice compared to immunocompetent C57BL/6 mice. CL-induced macrophage depletion promoted tumor proliferation and shortened survival in C57BL/6 mice (p=0.004) and in B6.129S7-Rag1tm1Mom/J mice (p=0.0005). During CL treatment, we observed a clear increase of pro-inflammatory cytokines (p≤0.02) and monocytic MDSC (p≤0.01). Selective depletion of MDSC by anti-GR1 improved survival, certainly in comparison to mice treated with anti-CSF1 (p=0.01 – median survival 91 vs 67.5 days). B6.129P2(SJL)-Myd88tm1.1Defr/J mice displayed to a longer median survival compared to C57BL/6 mice (90 vs 76 days). MDSC activated by ID8-fLuc conditioned medium or ascites of tumor-bearing mice showed T cell suppressive functions in vitro. Based on these findings, we conclude that the adaptive immune system does not efficiently control tumor growth in the ID8-fLuc model. In addition, we discovered a prominent role for MDSC as the driver of immunosuppression in the ID8-fLuc ovarian cancer mouse model.